Metabolic Syndrome as a Risk Factor of Endometrial Cancer: A Nationwide Population-Based Cohort Study of 2.8 Million Women in South Korea - Jo, HyunA; Kim, Se Ik; Wang, Wenyu; Seol, Aeran; Han, Youngjin; Kim, Junhwan; Park, In Sil; Lee, Juwon; Yoo, Juhwan; Han, Kyung-Do; Song, Yong Sang (Frontiers in Oncology, 2022)
Background: A positive relationship was reported between metabolic syndrome and the risk of endometrial cancer. Studies on the relationship between metabolic syndrome and endometrial cancer have been mainly conducted in post-menopausal women. We aimed to investigate the risk of endometrial cancer according to metabolic syndrome and menopausal status using the Korean nationwide population-based cohort. Methods: We enrolled 2,824,107 adults (endometrial cancer group; N = 5,604 and control group; N= 2,818,503) from the Korean National Health Insurance Service checkup database from January 1 to December 31, 2009. The median follow-up duration was 8.37 years. Metabolic syndrome was diagnosed as having at least three of the following five components: abdominal obesity, hypertriglyceridemia, low levels of high-density lipoprotein cholesterol, raised blood pressure, and hyperglycemia. Multivariate Cox proportional hazard models were used to calculate hazard ratios (HRs) with 95% confidence intervals (CIs) to estimate endometrial cancer risk. Results: The endometrial cancer risk was higher in the metabolic syndrome group than that in the non-metabolic syndrome group (HR, 1.362; 95% CI, 1.281–1.449). The association between metabolic syndrome and endometrial cancer risk was significant in the premenopausal subgroup (HR, 1.543; 95% CI, 1.39–1.713) and postmenopausal subgroup (HR, 1.306; 95% CI, 1.213–1.407). The incidence of endometrial cancer was more closely related to metabolic syndrome components in the pre-menopausal subgroup than those in the post-menopausal subgroup (for waist circumference, blood pressure, triglycerides and high-density lipoprotein cholesterol, all p for interaction <0.0001 respectively, and for fasting blood glucose, p for interaction 0.0188). The incidence of endometrial cancer positively correlated with the number of metabolic syndrome components (log-rank p <0.0001). Conclusion: Our large population-based cohort study in Korean women suggests that metabolic syndrome and its accumulated components may be risk factors for endometrial cancer, particularly in the pre-menopausal women.